2014
DOI: 10.4161/onci.29259
|View full text |Cite
|
Sign up to set email alerts
|

STING-dependent cytosolic DNA sensor pathways regulate NKG2D ligand expression

Abstract: The DNA damage response (DDR) upregulates the expression of NKG2D ligands (NKG2DLs).1,2 We have recently reported that the DDR also induces the presence of cytosolic DNA in B-cell lymphoma cells, which leads to the activation of STING-dependent cytosolic DNA sensor pathways and the expression of RAE-1 ligands for NKG2D.3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…Of note, as shown in studies on tumor models, DDR reportedly induces the expression of numerous class III DAMPs including MICs and different ULBPs through the activation of STING‐mediated pathways . Strikingly, the data suggest that DNA damage in lymphoma cells leads to the presence of class I DAMPs in form of cytosolic single‐stranded DNA and dsDNA.…”
Section: The Dna Damage Responsementioning
confidence: 66%
See 1 more Smart Citation
“…Of note, as shown in studies on tumor models, DDR reportedly induces the expression of numerous class III DAMPs including MICs and different ULBPs through the activation of STING‐mediated pathways . Strikingly, the data suggest that DNA damage in lymphoma cells leads to the presence of class I DAMPs in form of cytosolic single‐stranded DNA and dsDNA.…”
Section: The Dna Damage Responsementioning
confidence: 66%
“…Other lines of study lend support to the suggestion that DNA damage or DNA replication stress promotes release of aberrant DNA structures into the cytosol in the form of single‐stranded (ss) and double‐stranded (ds) DNA breaks that operate as class I DAMPs. They are sensed by the DNA receptor cyclic GMP‐AMP synthase and probably other as‐yet unidentified DNA receptors to activate stimulator of interferon genes (STING)–dependent pathways to promote defense pathways .…”
Section: The Dna Damage Responsementioning
confidence: 99%
“…However, this is not the only way whereby the transition from the adaptive arm of stress responses to the activation of RCD contributes to the maintenance of the entire organism. Indeed, both stressed and dying cells emit a large panel of signals that alert other cells of danger, including various cytokines and so-called "damage-associated molecular patterns" (DAMPs) [41][42][43].…”
Section: Regulated Cell Death and Organismal Homeostasismentioning
confidence: 99%
“…These data suggested that induced DNA damage, via the cytosolic DNA sensing pathway, upregulates NKG2D ligands in cell lines that express low amounts of ligands. Furthermore, DNA damage associated with tumorigenesis appears to also activate the cytosolic DNA sensing pathway and sustains constitutive expression of NKG2D ligands in tumor cells . The mediators that link the cGAS‐STING‐IRF3 pathway to NKG2D ligand expression on the cell surface remain to be established.…”
Section: Genomic Damage Regulates Nkg2d Ligandsmentioning
confidence: 99%
“…Furthermore, DNA damage associated with tumorigenesis appears to also activate the cytosolic DNA sensing pathway and sustains constitutive expression of NKG2D ligands in tumor cells. [40][41][42] The mediators that link the T A B L E 1 Regulation of cellular expression of NKG2D ligands by stress pathways F I G U R E 1 Summary of pathways and signals discussed in this review that induce NK cell activation and/or NKG2D ligand expression in tumor cells and in virus-infected cells. The pathways include the DNA damage response, the cGAS-STING pathway, proliferative signals, PI3-kinase activity, dysregulation of histone acetylation, and the integrated stress response.…”
Section: Genomic Damage Regulates Nkg2d Ligandsmentioning
confidence: 99%